PERCEPÇÃO DE SUPORTE SOCIAL E CONSUMO DE ÁLCOOL EM DESEMPREGADOS - Bezerra-ribeiro, Mônica (2008)
The unemployment has always been the object of concern in the political, economic and social context. The unemployed people face daily difficulties finding jobs; this situation generates great emotional stress and can negatively affect the health of the worker. This Study has the objective of investigate the perception of social support and the consumption of alcohol among unemployed people. Through the epidemiological, quantitative and cross sectional study of 300 individuals enlisted in a public agency located in São Bernardo do Campo SP, the agency operates looking for job openings and send the workers to professional repositioning on the market. The sample resulted in a group where 54,3% were male, with an average age of 29 to 30, ranging from 18 to 56 years old, 67% had high school level and 50% were single, 52% were unemployed for 6 months, 37% lived in their own house, and 37% had a combined household income from one to two minimum wages. Three self applied instruments were used for data gathering. a) Social Demographic Characteristic Questionnaire; b) Perceived Social Support Scale (PSSS); c) Alcohol Use Disorders Identification Test (AUDIT). The collected data was submitted to the Statistical Package for Social Sciences (SPSS) version 15.0 for Windows that allowed to make the correlation between the variables. The result indicated significant correlation between variables: Practical support and income; Practical and emotional support with age. These correlations suggested that the subjects presented better perception of practical support as their household income grew, and that the older they were the smaller was their perception of practical and emotional support received from the social network. The AUDIT did not show any significant correlation between the studied variables, and 76% of the sample fell in the zone 1 (low risk consumption or abstinence). We did not find any correlation between alcohol consumption and unemployment.(AU)